The Effect of Traditional Games on the Social health of Tunisian Pupils in Physical Education - BEN AMAR, Imen; GHAYAZA, Nizar; CHERIF, Aicha; ELLOUMI, Ali (Advances in Social Sciences Research Journal, 2020)
By positioning itself as clearly in the niche market of health, physical education tries to make its contribution vis-à-vis a set of problems representing significant social costs. Several experiments of promotion of the physical activities with purpose hygienic were realized abroad. The Scandinavian countries, Quebec and the USA became famous in this particular approach. In Tunisia, in spite of an official report on this published subject there was about fifteen years, no overall policy was defined. The introduction, for the school physical education, of an objective of preparation for the adult's physical life evoking explicitly the problem of the management of the health, allows to fill partially, at least from the point of view of the principles, this deficiency. In this study, we shall try review of the effects of the traditional sports games on the health of the pupil. It will be a question of arguing in a most objective possible way the links positive which we can weave between game and social health.